Sampling strategy of an epidemiological survey using a satellite image program - Ticiane de Góes Mário Ferreira; José Mariano da Rocha; Silvia Cardoso de David; Jociana Boligon; Maísa Casarin; Alessandra Pascotini Grellmann; Janice Marin; Thiago Machado Ardenghi; Fabricio Batistin Zanatta; Carlos Heitor Cunha Moreira (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE To describe the sampling strategy of an epidemiological survey with the aid of satellite images, including details of the multistage probability sampling process. METHODS A probability sample of individuals living in the rural area of Rosário do Sul, state of Rio Grande do Sul, Brazil, aged 15 years old or more, was evaluated. Participants answered questionnaires (medical history, sociodemographic characteristics, habits, alcohol use, quality of life, stress, rumination, and self-perceived periodontal diseases), and were subjected to clinical oral examinations as well as anthropometric measurements (blood pressure, height, weight, abdominal and waist circumferences). Oral evaluation comprehended a complete periodontal exam at six sites per tooth, including the following assessments: furcation involvement; dental abrasion; tooth decay, including the indexing of missing and filled surfaces; O'Brien index; gingival abrasion; oral cavity and lip lesions; complete periapical radiographic exam, and use of prostheses. Besides this oral clinical approach, subgingival plaque, crevicular gingival fluid, saliva, and blood samples were collected. Examiners were trained and calibrated during previous evaluations. A pilot study allowed the logistic of the performed exams to be adjusted as needed. RESULTS Among 1,087 eligible individuals, 688 were examined (63.3%). Age, sex, and skin color data were compared to data from the last demographic census (2010) of the Brazilian Institute of Geography and Statistics, which served to validate the sampling strategy. CONCLUSIONS The careful methods used in this study, in which satellite images were used in the delimitation of epidemiological areas, ensure the quality of the estimates obtained and allow for these estimates to be used in oral health surveillance and health policies improvements.